La réduction de facteurs de risque de chronicité et le retour au travail - Michael Sullivan; Heather Adams; William Stanish; André Savard (Perspectives Interdisciplinaires sur le Travail et la Santé)
The purpose of the present study was to examine the degree to which psychosocial risk factor reduction was associated with the return to work. This study was carried out in the context of a rehabilitation program for workers who had suffered a back injury. The participants were 116 Nova Scotia WCB claimants (68 men, 48 women) who had made a claim for an industrial accident. The participants were oriented towards a cognitive behavioral intervention whose purpose was to reduce psychological obstacles to rehabilitation. The psychosocial risk factors targeted by the program included pain catastrophizing, fear of movement, beliefs about disability, and depression. In this sample, 56 % of the participants returned to work within four weeks of treatment termination. Pre- to post-treatment comparisons revealed significant reductions in pain, depression, catastrophizing, perceived disability, and fear of movement. Univariate analyses revealed that reductions in all risk factors were associated with a higher probability of a return to work. Logistic regression revealed that only the duration of work disability and the reduction in pain catastrophizing contributed solely to the prediction of a return to work. The results of the present study provide preliminary evidence that the reduction of psychosocial risk factors related to chronicity may have a positive impact on the probability of returning to work.